2010
DOI: 10.1037/a0018582
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress in Canadian universities: A national survey.

Abstract: Stress surveys in U.K. and Australian universities demonstrated high occupational stress levels among faculty. This study investigated whether the same occupational stressors and stress outcomes applied at Canadian universities. Randomly selected staff (n ϭ 1440) from 56 universities completed a Web-based questionnaire. The response rate 27%, was similar to those in the U.K. and Australian studies, as were most of the results. With respect to strain, 13% of the respondents reported high psychological distress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
142
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(160 citation statements)
references
References 25 publications
11
142
0
7
Order By: Relevance
“…However, there was no difference in mean levels of work-life conflict reported by men and women. Consistent with the findings of Cantano et al (2010), women in the current study reported significantly higher psychological strain than men. Women also reported higher organisational expectations to work long hours, higher work intensity, higher organisational support, lower work enjoyment and lower job involvement than men.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, there was no difference in mean levels of work-life conflict reported by men and women. Consistent with the findings of Cantano et al (2010), women in the current study reported significantly higher psychological strain than men. Women also reported higher organisational expectations to work long hours, higher work intensity, higher organisational support, lower work enjoyment and lower job involvement than men.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Cantano et al (2010) found that female academics had higher levels of work-life conflict than male academics, whereas, Winefield et al (2008) found that male academics reported higher levels of work-life conflict than female academics. Byron (2005) suggested that different factors may influence levels of work-life conflict in men and women, however, no study to date has examined these differences.…”
Section: Extending the Rational Model Of Work-life Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research indicates that the effort that academics are required to put into their job can engender conflict between work and personal life, which can be a considerable source of distress (Kinman & Jones, 2008;Winefield, Boyd, & Winefield, 2014). Nonetheless, although academic work can be demanding and stressful, there is also evidence that it can be satisfying and rewarding (Bentley et al, 2013;Catano et al, 2010). Factors such as autonomy, variety, role clarity, intellectual challenge, collegiality, contribution to society, respect from colleagues and managers, and the ability to gain self esteem from professional reputation, have been cited as particularly powerful sources of satisfaction for academics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Catano et al, 2010;Coetzee & Rothmann, 2005;Kinman, Jones & Kinman, 2006;Tytherleigh, Webb, Cooper, & Ricketts, 2005;Winefield, Boyd, Saebel, & Pignata, 2008). Research that has tracked the work-related wellbeing of academics working in the United Kingdom (UK) over several years (from 2008 to 2014) suggests that the demands experienced by academics have increased over time and the resources that have traditionally protected them from work-related stress, such as autonomy, support and role clarity, have eroded (Kinman & Wray, 2015).…”
Section: Introductionmentioning
confidence: 99%